2019
DOI: 10.1002/ange.201811391
|View full text |Cite
|
Sign up to set email alerts
|

Gasotransmitter Regulation of Phosphatase Activity in Live Cells Studied by Three‐Channel Imaging Correlation

Abstract: Enzyme activity in live cells is dynamically regulated by small‐molecule transmitters for maintaining normal physiological functions. A few probes have been devised to measure intracellular enzyme activities by fluorescent imaging, but the study of the regulation of enzyme activity via gasotransmitters in situ remains a long‐standing challenge. Herein, we report a three‐channel imaging correlation by a single dual‐reactive fluorescent probe to measure the dependence of phosphatase activity on the H2S level in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The Stern‐Volmer linear equation was ( F 0 ‐ F ) = 5.308 [Cu 2+ ] − 21.96 with a correlation coefficient R 2 of.997, indicating excellent analytical ability in detecting Cu 2+ with a wider detection range. The LOD was calculated to be 1.0nM (S/N = 3) and was much lower than that of previously reported fluorescence CDs probes from other green natural carbon sources (Table ). The wider detection range and lower LOD fully demonstrated that the present N‐CDs from crown daisy leaves were an ideal fluorescent sensor in the detection of Cu 2+ .…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…The Stern‐Volmer linear equation was ( F 0 ‐ F ) = 5.308 [Cu 2+ ] − 21.96 with a correlation coefficient R 2 of.997, indicating excellent analytical ability in detecting Cu 2+ with a wider detection range. The LOD was calculated to be 1.0nM (S/N = 3) and was much lower than that of previously reported fluorescence CDs probes from other green natural carbon sources (Table ). The wider detection range and lower LOD fully demonstrated that the present N‐CDs from crown daisy leaves were an ideal fluorescent sensor in the detection of Cu 2+ .…”
Section: Resultsmentioning
confidence: 56%
“…[Cu 2+ ] − 21.96 with a correlation coefficient R 2 of.997, indicating excellent analytical ability in detecting Cu 2+ with a wider detection range. The LOD was calculated to be 1.0nM (S/N = 3) and was much lower than that of previously reported fluorescence CDs probes from other green natural carbon sources 5,7,9,31,39,[42][43][44][45][46][47][48][49][50][51] (Table 1) experiments of the prepared probe toward Cu 2+ were carried out after the probe was stored at 4°C in a refrigerator for 7 days to study its measurement stability, and the result showed no observable change in fluorescence signals, which proved that the prepared N-CD probe had high measurement stability toward Cu 2+ .…”
Section: Sensing Application Of the Prepared N-cdsmentioning
confidence: 58%
See 2 more Smart Citations
“…Ou et al (22) reported a dual-reactive fluorescent probe, N 3 -CR-PO 4 , which can detect phosphatase activity and H 2 S at the same time (Fig. 3B); this is useful because H 2 S is thought to be a regulator of phosphatase activity.…”
Section: Recent Developments In Fluorescent Probes For H 2 Smentioning
confidence: 99%